A sarabande of tropical fruit proteomics: Avocado, banana, and mango. Issue 10 (5th February 2015) - Righetti, Pier Giorgio; Esteve, Clara; D'Amato, Alfonsina; Fasoli, Elisa; Luisa Marina, María; Concepción García, María; Lüthje, Sabine; Deswal, Renu; Agrawal, Ganesh Kumar
<x xml:space="preserve">Abstract</x> The present review highlights the progress made in plant proteomics via the introduction of combinatorial peptide ligand libraries (CPLL) for detecting low‐abundance species. Thanks to a novel approach to the CPLL methodology, namely, that of performing the capture both under native and denaturing conditions, identifying plant species in the order of thousands, rather than hundreds, is now possible. We report here data on a trio of tropical fruits, namely, banana, avocado, and mango. The first two are classified as "recalcitrant" tissues since minute amounts of proteins (in the order of 1%) are embedded on a very large matrix of plant‐specific material (e.g., polysaccharides and other plant polymers). Yet, even under these adverse conditions we could report, in a single sweep, from 1000 to 3000 unique gene products. In the case of mango the investigation has been extended to the peel too, since this skin is popularly used to flavor dishes in Far East cuisine. Even in this tough peel 330 proteins could be identified, whereas in soft peels, such as in lemons, one thousand unique species could be detected.